1988
DOI: 10.1093/clinchem/34.4.724
|View full text |Cite
|
Sign up to set email alerts
|

A high-performance liquid-chromatographic method for routine simultaneous determination of nicotine and cotinine in plasma.

Abstract: We describe a rapid, sensitive method for the routine simultaneous determination of nicotine and cotinine in 1 mL of plasma. Extraction in 10-mL screw-capped Teflon tubes with methylene chloride after deproteinization with trichloroacetic acid eliminated emulsion formation. The extract, after evaporation and reconstitution in 30 microL of mobile phase, is injected into a reversed-phase C-18 ion-pair column of an isocratic high-performance liquid-chromatographic unit. Absorbance is monitored at 256 nm. The mobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

1990
1990
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(36 citation statements)
references
References 0 publications
0
36
0
Order By: Relevance
“…Cotinine assay was performed in blinded fashion by reversed-phase C-18 ion-pair high performance liquid chromatography (HPLC) and detection by absorbance at 256 nanometers using a modified Hariharan, VanNoord, and Greden ( 1988) protocol. Reported intra-assay coefficients of variations (CVs) were 2.3 to 5.8% and interassay CVs were 2.4 to 5.5%, while extraction efficiency for cotinine standard was 84% (Hariharan et al, 1988). In this study, average within run CV for cotinine assay was 7.6%.…”
Section: Methodsmentioning
confidence: 99%
“…Cotinine assay was performed in blinded fashion by reversed-phase C-18 ion-pair high performance liquid chromatography (HPLC) and detection by absorbance at 256 nanometers using a modified Hariharan, VanNoord, and Greden ( 1988) protocol. Reported intra-assay coefficients of variations (CVs) were 2.3 to 5.8% and interassay CVs were 2.4 to 5.5%, while extraction efficiency for cotinine standard was 84% (Hariharan et al, 1988). In this study, average within run CV for cotinine assay was 7.6%.…”
Section: Methodsmentioning
confidence: 99%
“…Plasma arterial nicotine and cotinine samples were determined before, 2, 10, and 45-60 min after bolus plus nicotine infusions using the HPLC methods of Hariharan et al (1988).…”
Section: Nicotine Assaymentioning
confidence: 99%
“…We studied 20 normal non-smoking control subjects and 71 asthmatic patients attending the Tsukidate Municipal Hospital. In order to exclude current smokers, we measured urinary cotinine concentration with high-performance liquid chromatography as described by Harlharan et al [12]. We found that urinary cotinine concentrations of all control and asthmatic subjects were less than 30 ng of the cotinine/mg creatinine ratio, the level used to categorize subjects as exposed and unexposed to cigarette smoking [13].…”
Section: Subjectsmentioning
confidence: 99%